Peningkatan Literasi dan Pengelolaan Keuangan bagi Ibu Rumah Tangga - Sari, Widya; Fadillah, Fadel Fadillah; Zahra, Syifa Amaliah; Liana, Rista Ade Liana (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
Family well-being can be influenced by financial management within the family. Financial management is a series of steps to maximize income and minimize expenses, while ensuring sufficient funds to meet daily needs. A preliminary survey revealed that the financial literacy level of mothers in Margaluyu Village, Pangalengan District, remains low and needs improvement. They lack an understanding of financial planning and are not yet effectively managing household finances. This community service method uses Participatory Action Research and Service Learning. Both methods are used complementary. The Financial Management Seminar was held on July 28, 2025, in Margaluyu Village, Pangalengan District, with 31 seminar participants. The majority of people in the village are vegetable farmers and workers in other people's businesses, followed by various other professions. Therefore, the material presented is general and can be applied in various households. It began with the delivery of financial literacy material, followed by financial planning and household financial management. The activity went well and smoothly. The majority of participants expressed their satisfaction with this community service activity. The results of this activity showed that participants were able to understand the scale of priorities, as well as ways to carry out financial planning and household financial management. .